Constitutional Rights of State Civil Apparatus in Politics in Indonesia - Ulfatussakinah Ulfatussakinah; Sodikin Sodikin (Jurnal Impresi Indonesia, 2025)
The guarantee of the political rights of the State Civil Apparatus (ASN) in the 1945 Constitution is further regulated in Law Number 20 of 2023 concerning the State Civil Apparatus (ASN) and various derivative regulations. This research aims to answer a fundamental question: how are the constitutional rights of the State Civil Apparatus (ASN) regulated in Indonesian politics, and what is their neutrality concerning the potential conflict between the constitutional guarantees of political rights in the 1945 Constitution and the restrictions on political activities imposed on the State Civil Apparatus (ASN) by legislation. This study employs a descriptive-normative method, utilizing both legislative and conceptual approaches. The findings indicate that the lack of synchronization between regulations and the unclear boundaries between active and passive political activities have generated normative tensions. These tensions arise between the constitutional rights of the State Civil Apparatus (ASN) and their obligation to maintain bureaucratic neutrality. Overly broad restrictions may violate the principle of proportionality and create legal uncertainty for the State Civil Apparatus (ASN). Additionally, this situation allows for varying interpretations among different agencies, leading to inconsistencies in the application of the principle of neutrality in practice. Consequently, it may undermine the political rights of the State Civil Apparatus (ASN) as citizens.